Enhanced Durability of Linker-Containing Carbon Nanotube Functionalized via Diazonium Reaction. (1st February 2015) - Kim, Jun Young; Kim, Yeon Su; Lee, Sungchul; Pak, Chanho; Kim, Hee-Tak
Abstract: We present the fabrication of highly durable catalysts with the functionalized carbon nanotube (CNT) via diazonium chemistry for polymer electrolyte membrane fuel cell (PEMFC). The functionalization of the CNT with the thiolphenyl groups by diazonium coupling reaction was shown to enhance the dispersion of Pt nanoparticles with narrow size distribution deposited on the CNT surfaces as well as their electrochemical stability. The electrochemical analysis demonstrates that the Pt/functionalized CNT show higher electrochemical durability and catalytic activity than the Pt/unmodified CNT. The enhanced electrochemical performance of the Pt/functionalized CNT is attributed to the uniform distribution of Pt nanoparticles with smaller size and the strong interaction between Pt and the functionalized CNT support through the formation of Pt-sulfur bonding. This study shows that this simple functionalization of CNT by the in situ grafting of the thiolphenyl groups as the linker onto the surface is an effective way to fabricate a highly durable Pt catalyst for PEMFC, thus providing a design guide of the functionalized CNT support catalyst with a great potential as a PEMFC catalyst.